2006
DOI: 10.1089/jpm.2006.9.683
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for the Death of a Loved One and Mental Health in Bereaved Caregivers of Patients with Dementia: Findings from the REACH Study

Abstract: Despite providing high-intensity care, often for years, many bereaved caregivers perceived themselves as unprepared for the death. These caregivers had more depression, anxiety, and complicated grief symptoms. Future work should be directed to confirming these findings and determining how best to intervene with high-risk caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 36 publications
8
179
2
3
Order By: Relevance
“…All participants were prior caregivers, and therefore the results may not be generalizable to more diverse samples because of the participants' caregiving experience before death, particularly at the end of the life stage. According to a recent study, many caregivers anticipate and grieve prior to the death of their relatives 21 . It is possible that grieving before death influences the level of complicated grief after death.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were prior caregivers, and therefore the results may not be generalizable to more diverse samples because of the participants' caregiving experience before death, particularly at the end of the life stage. According to a recent study, many caregivers anticipate and grieve prior to the death of their relatives 21 . It is possible that grieving before death influences the level of complicated grief after death.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that preparing families for death is a way to improve care. This approach is further validated by a study that showed that prepared families suffered from less depression and complicated grief [132], and acknowledgment as a terminal illness may also benefit patients ( Table 1).…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…As palliative care is shifting from the hospital to the community and the home, there is a need for more research focused on understanding informal family caregivers' knowledge and information needs (Docherty et al, 2008). Providing cross-cultural and culturally appropriate information on hospice and end-of-life care will help health professionals enrich communication and provide anticipatory guidance and preparedness for Hawai'i's family caregivers regarding end-of-life care (Hebert, Dang, & Schulz, 2006). Providing cross-cultural strategies to support, inform, and prepare family caregivers will lead to positive consequences and outcomes.…”
Section: Discussionmentioning
confidence: 99%